Association of diabetes with tooth loss in Hispanic/Latino adults: findings from the Hispanic Community Health Study/Study of Latinos. Issue 1 (12th May 2016) - Greenblatt, Ariel P; Salazar, Christian R; Northridge, Mary E; Kaplan, Robert C; Taylor, George W; Finlayson, Tracy L; Qi, Qibin; Badner, Victor
Abstract : Objectives: To investigate the association between diabetes mellitus and missing teeth in Hispanic/Latino adults from diverse heritage groups who reside in the USA. Research design and methods: The Hispanic Community Health Study/Study of Latinos (HCHS/SOL) is a multicenter, population-based study of 18–74 years old who underwent a physical and oral examination (n=15 945). Glycemic status was categorized as diabetes, impaired, or normal, based on medication use, and American Diabetes Association criteria for fasting glucose and glycosylated hemoglobin (HbA1c). HbA1c<7% indicated good glycemic control, and HbA1c> 7% indicated uncontrolled diabetes. We estimated ORs and 95% CIs for missing > 9 teeth and being edentulous (missing all natural teeth), after adjustment for age, income, education, Hispanic background, study site/center, nativity, last dental visit, health insurance, diet quality, cigarette smoking, obesity, periodontitis, and C reactive protein. Results: Persons with uncontrolled diabetes had a significant increased likelihood of missing > 9 teeth and being edentulous as compared with persons with normal glycemic status (adjusted OR=1.92, 95% CI 1.44 to 2.55 and adjusted OR=1.73, 95% CI 1.22 to 2.46, respectively). The association appeared to be stronger at younger ages (18–44 years old; p for interaction <0.0001). However, we found no associations of either impaired glycemia or controlled diabetes with tooth loss in adjusted models. Conclusions: Dentists should be aware of their Hispanic patients' diabetes status and whether or not they are well controlled, because these may affect tooth loss and impair oral function, which can lead to poor nutrition and complications of diabetes.